Utilizing Problem-Based Learning to Develop Speaking Skill - Farah Humairah Fatimah; Aminah Suriaman; Andi Patmasari; Mochtar Marhum (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Speaking skills are one of the basic language skills that play an important role in oral communication. There are several problems with learning to speak experienced by the eighth-grade students at SMP Negeri 14 Palu. The problem is that students lack vocabulary, which makes it difficult to speak. In addition, students’ lack of confidence hinders their ability to communicate using English during the English learning process. Therefore, the purpose of this research is to prove that the utilizing of problem-based learning can improve the student’s speaking skill of the eighth-grade students at SMP Negeri 14 Palu. To answer the problems above, researchers used a quasi-experimental research design with cluster random sampling to choose the sample. The population of this research were students from grade eight students at SMP Negeri 14 Palu. The samples of this research were students of grade VIII Pattimura as the experimental group and grade VIII Jenderal Sudirman as the control group. To obtain data, the researchers used YouTube as a learning medium and a voice recorder as an instrument to obtain answers from students. The results of this research prove that the implementation of problem-based learning can improve students’ speaking skill in the VIII Pattimura. The results of this research can help teachers find a new method that is designed to make students actively participate in expressing their ideas and opinions in English.